1992
DOI: 10.1136/oem.49.6.428
|View full text |Cite
|
Sign up to set email alerts
|

Signs of alveolar inflammation in non-smoking Swedish wood trimmers.

Abstract: Wood trimmers are periodically exposed to mould and may develop extrinsic allergic alveolitis (EAA). To investigate if there were any signs of EAA in wood trimmers with low exposure, 19 non-smoking wood trimmers underwent bronchoalveolar lavage (BAL), spirometry, and measurement of diffusion capacity (TLco). The group was subdivided into those with (n = 9) and without serological antibodies against mould. In 14 workers the TL,0 was measured both at the beginning and at the end of a week at work. Twenty five he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…On the basis of eight studies from the work place wood processing with different effect endpoints no studies for the derivation of exposure limits could be identified mainly due to insufficient exposure data (V1) (Avila and Lacey, 1974;Dahlqvist et al, 1992;Dahlqvist and Ulfvarson, 1994;Johard et al, 1992;Mandryk et al, 1999Mandryk et al, , 2000Schlünssen et al, 2011), no evaluation of dust measurements (V2) (Avila and Lacey, 1974;Dahlqvist et al, 1992) and inconsistent results of statistical analyses (V3) (Mandryk et al, 1999(Mandryk et al, , 2000. Mandryk et al analyzed correlations (Pearson's R) among mean personal exposures.…”
Section: Validity Assessment Of Wood Processing Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…On the basis of eight studies from the work place wood processing with different effect endpoints no studies for the derivation of exposure limits could be identified mainly due to insufficient exposure data (V1) (Avila and Lacey, 1974;Dahlqvist et al, 1992;Dahlqvist and Ulfvarson, 1994;Johard et al, 1992;Mandryk et al, 1999Mandryk et al, , 2000Schlünssen et al, 2011), no evaluation of dust measurements (V2) (Avila and Lacey, 1974;Dahlqvist et al, 1992) and inconsistent results of statistical analyses (V3) (Mandryk et al, 1999(Mandryk et al, , 2000. Mandryk et al analyzed correlations (Pearson's R) among mean personal exposures.…”
Section: Validity Assessment Of Wood Processing Studiesmentioning
confidence: 98%
“…Reference 1 2 3 4 5 6 7 8 Avila and Lacey (1974) NV NV (-) NV (-) (-) (-) (-) Johard et al (1992) NV (-) (-) (-) (-) NV (-) (-) Dahlqvist et al (1992) NV NV (-) (-) (-) NV (-) (-) Dahlqvist and Ulfvarson (1994) Roponen et al (2003) NV NV (-) (-) NV NV (-) (-) NV, not valid; V, valid; (-), not assigned. measurement methods for endotoxins and ␤-glucans are not standardized for environmental settings to date these studies were excluded.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The occupational exposure limit in Sweden at present is 150 mg/m3 for both total and individual monoterpenes (3, and in sawmills the exposure often exceeds this limit (1,(6)(7). Sawmill workers exposed to monoterpenes and wood dust have been shown to respond with airway symptoms, a decrease in lung function, and airway inflammation, the last-mentioned being reflected by bronchoalveolar lavage (BAL) results (6)(7)(8)(9)(10)(11). After the reduction of sawing fumes in a Swedish sawmill, an 8-year follow-up study was expected to show relative improvement in lung function among the employees working in the saw shed (12).…”
mentioning
confidence: 99%
“…Research studies have pointed out that acute exposure to WDs is associated with an increased blood count of eosinophils whereas bronchoalveolar lavage (BAL) and nasal lavage (NAL) show an increased cellularity, predominantly neutrophils and T cell lymphocytes, with increased expression of inflammatory mediators [29][30][31][32]. At alveolar level, WDs are also able to elicit an intense inflammatory reaction, with highSelected axial slices through the lower lung fields (a-c) show diffuse peripheral reticular opacities in a pattern of distinctive and diffuse honeycombing.…”
Section: Discussionmentioning
confidence: 99%